HoLEP does not affect the overall sexual function of BPH patients: a prospective study - Sung Han Kim; Hyung-Kook Yang; Hahn-Ey Lee; Jae-Seung Paick; Seung-June Oh (Asian Journal of Andrology, 2014)
We aimed to prospectively evaluate the influence of holmium laser enucleation of the prostate (HoLEP) on the overall postoperative sexual function of benign prostatic hyperplasia (BPH) patients with lower urinary tract symptoms (LUTS) and to explore the relationship between sexual function and LUTS. From January 2010 to December 2011, sixty sexually active consecutive patients with BPH who underwent HoLEP were prospectively enrolled in the study. All patients filled out the Male Sexual Health Questionnaire (MSHQ) for evaluation of their overall sexual function and the International Prostatic Symptom Score (IPSS) for pre- and post-operative 6 months evaluation of their voiding symptoms. The LUTS and sexual function changes were statistically analyzed. The preoperative and 6 months postoperative status of the patients was compared using uroflowmetry and IPSS questionnaires. The analysis revealed significant improvements following HoLEP. Among the sub-domains of the MSHQ, postoperative sexual function, including erection, ejaculation, sexual satisfaction, anxiety or sexual desire, did not significantly change after HoLEP (P > 0.05), whereas satisfaction scores decreased slightly due to retrograde ejaculation in 38 patients (63.3%). Sexual satisfaction improved significantly and was correlated with the improvements of all LUTS and the quality-of-life (QoL) domains in IPSS after surgery (QoL; relative risk [RR]: −0.293; total symptoms, RR: −0.411; P < 0.05). The nocturia score was associated with the erectile function score (odds ratio 0.318, P = 0.029). The change in ejaculatory scores did not show significant association with IPSS scores. HoLEP did not influence overall sexual function, including erectile function. In addition, sexual satisfaction improved in proportion with the improvement of LUTS.